Comparative Economics of Traditional viz. High Density Mango Cultivation in Karnataka - Kerutagi, M. G.; Deshetti, M. B. (Indian Journal of Hill Farming, 2018)
The present study estimates the growth in the area, production and productivity of mango, assesses the cost and return structure and to analyze the financial feasibility of Mango cultivation in Dharwad district of Karnataka state. Sixty sample farmers from Dharwad district were randomly selected for eliciting required information for the study at the rate of 30 each from traditional and high-density orchard of Dharwad taluk. The study reveals that the area and production of mango in Dharwad district showed positive growth. Total annual maintenance cost of traditional mango (.21,783/ ha) was lower compared to HDP (48,132/ha). Mango is harvested in a single season in a year. In high-density orchard, the average yield obtained was more (7.86t/Ac) than in traditional orchard (3.50/t/Ac). However, the sale price was Rupees.90,950, Rupees 2,04,320 in both traditional and high-density orchard respectively. Pay Back Period was found to be higher in traditional i.e. 5.90 years whereas in high-density orchardit was 5.54 years. NPV at 12 percent discount rate for the entire life period of the Mango (30 years) was Rupees 1,16,032.25 and Rupees. 4,34,686.29 in traditional and HDP, respectively. The Benefit cost ratio was 1.49 and 2.00 in traditional and HDP respectively. The internal rate of returns was calculated to be 18.20 percent in traditional Orchard, while in the case of high-density planting, it was 26.00 percent. Therefore, investment in Mango was financially feasible in both the type of cultivation.